Pengaruh Penambahan Limbah Ampas Kopi Sebagai Pengganti Filler Pada Campuran Lapis Tipis Aspal Beton (Lataston) Dengan Perendaman Berulang - Pondy, Muh Fadly Noor; Nurdin , Abd Rahim; Yunianti, Nurhadijahs (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
This research was conducted using hot asphalt (HRS-WC) with coffee grounds waste as a partial filler replacement in asphalt mixtures. The purpose of this research is to analyze the characteristics of hot asphalt mixtures (HRS-WC) using hot asphalt with variations of coffee grounds waste as a partial filler replacement with repeated immersion. This study used coffee grounds waste with an accumulation of 20%, 25% and 30% of the filler weight. The soaking times in this study were 3, 7, and 14 days with repeated soaking. The manufacture of test specimens refers to the 2018 Bina Marga Specification. Testing using the Marshall Test. In the addition of coffee grounds waste as a partial substitute for filler as much as 20%, 25% and 30% of the asphalt mixture properties meet the limits of the 2018 Bina Marga Specifications. The best value in the properties of the asphalt mixture in this study is 20% at 3 days immersion, while the 30% mixture does not meet one of the properties of the asphalt mixture, namely the VIM value which is not within the specification limits.